Simultaneous determination of tartrazine (E 102) and brilliant blue FCF (E 133) at modified electrodes; Theoretical and experimental chemistry - Lipskikh O. I. Olga Ivanovna (Contemporary issues of theoretical and experimental chemistry, 2017)
Title screen